The Continuing Education Network and the training of educators in the Municipal Network of the State of Espírito Santo: Introduction to Brazilian Sign Language - Lisboa Diniz, Kelly Christine (Guará Journal, 2025)
This paper addresses the issue of continuing education in the contemporary educational context as a way to rethink how to improve the quality of education in the country and professional qualifications in the classroom. We use the MEC (Municipal Education and Training Network) program as a guiding principle to guide our observations. It is not only the role of professionals to be aware that their education does not end with a degree, but also that it is the responsibility of competent public agencies to motivate their educators and provide support so that they can continually improve their qualifications to meet the demands and needs of their students. Based on the program's experience, we believe that training (or retraining) education professionals through continuing education provides both professional independence and autonomy to decide on their work and their ongoing research needs.
Keywords: Continuing education; Teacher; CEFOCO; Libras